VoxelSky-3D: A Weather Radar Visualization Prototype for Air Traffic Control - Zhenhao Zhan; Tek-Yong Lim; Kannan Ramakrishnan (IEEE Access)
This paper presents VoxelSky-3D, a new 3D weather radar visualization prototype for civil aviation air traffic control. While previous research has explored text-based, image-based, and some three-dimensional meteorological displays, none have fully integrated voxelization techniques to deliver real-time, comprehensive 3D weather visualizations specifically tailored for Air Traffic Control Officers (ATCOs). The lack of traditional 2D weather radar displays vertical atmospheric structures for ATCOs, which are critically important for safety and efficiency during flight. VoxelSky-3D is an auxiliary system that uses voxelization to transform weather radar data into 3D voxel-based representations. The methods used in this study include the conversion of coordinates, voxelizing of the geographic coordinate system, and integration with Geographic Information Systems for rendering via the Web Graphics Library. The experimental results verified that VoxelSky-3D is an effective application for visualizing weather radar data in 3D, which directly provides ATCOs with intuitive views of the vertical atmospheric conditions. The performance test results revealed that the system could build real-time complex 3D weather scenes and provide high frame rates under relatively high volumes of incoming data. The VoxelSky-3D prototype is a considerable step forward in the field of meteorological data visualization for air traffic control, which improves the situational awareness and decision-making capabilities of ATCOs.